HOME REHABILITATION PROGRAM IN THE CASE OF BELL'S PALSY AT Dr.EFRAM HARSANA Hospital, ISWAHJUDI-Case Report - Wulandari, Tri Mei; Widodo, Agus (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Bell's palsy is a unilateral facial nerve with rapid onset of weakness or paralysis of unknown cause. The facial paralysis that occurs in Bell's palsy can cause significant transient oral incompetence and an inability to close the eyelids, leading to potential eye injury.Case Presentation: The method used in this study is a case study. This case study was conducted at Dr. Efram Harsana Hospital with the patient Mrs. S with the age of 67 years. Management and outcome: the provision of infrared, electrical stimulation, and mirror exercise is one of the effective methods to increase muscle strength and improve the functional ability of facial muscles. Discussion: The IR application given to Bell's palsy patients will have a relaxing effect and help drain blood in the area. Giving electrical stimulation, namely electrochemical reactions, membrane permeability, reactions to motor nerves in the form of skeletal muscle contractions, increasing muscle strength, improving the vascular system and stimulating sensory nerves. This type of mirror exercise aims to increase facial muscle strength and increase facial functional ability activity. Conclusion: Physiotherapy treatment in the form of IR, electrical stimulation, and mirror exercise can increase muscle strength and improve the functional ability of facial muscles.